Empowerment of Sekar Dewata Dance and Painting Studio for Diffable Children - I Gusti Agung Ayu Istri Lestari; Ida Ayu Nyoman Yuliastuti; I Wayan Eka Artajaya; I Gede Cahyadi Putra (Journal of the Community Development in Asia (JCDA), 2019)
Sekar Dewata is a non-formal arts institution, and has become one of the activities for diffable children. The problems faced by Sekar Dewata studio are the lack of uniforms for dance and painting practice, the absence of dance clothes for staging, the quality of folding tables used for painting practice are still relatively low, and do not yet have dance teaching standards for deaf children. The results obtained from this dedication activity are the process of dancing and painting practice running more effectively and comfortably, dance staging clothes do not need to be rented anymore, the quality of the tables used in painting exercises are not perishable, and there are operational standard dance procedures that facilitate dance instructors in training deaf child.